2008
DOI: 10.1074/jbc.m707009200
|View full text |Cite
|
Sign up to set email alerts
|

β2-Adrenergic Receptor Signaling and Desensitization Elucidated by Quantitative Modeling of Real Time cAMP Dynamics

Abstract: G protein-coupled receptor signaling is dynamically regulated by multiple feedback mechanisms, which rapidly attenuate signals elicited by ligand stimulation, causing desensitization. The individual contributions of these mechanisms, however, are poorly understood. Here, we use an improved fluorescent biosensor for cAMP to measure second messenger dynamics stimulated by endogenous ␤ 2 -adrenergic receptor (␤ 2 AR) in living cells. ␤ 2 AR stimulation with isoproterenol results in a transient pulse of cAMP, reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
227
1
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 232 publications
(244 citation statements)
references
References 36 publications
14
227
1
2
Order By: Relevance
“…3A), where receptor desensitization would occur with CCL19. Furthermore, there are some indications that receptor desensitization could take place in a ligand specific manner (8) as described for other seven-transmembrane receptors (47). As mature DCs are secreting CCL19, CCL19-specific desensitization might be also responsible for the observed CCL21 preference (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…3A), where receptor desensitization would occur with CCL19. Furthermore, there are some indications that receptor desensitization could take place in a ligand specific manner (8) as described for other seven-transmembrane receptors (47). As mature DCs are secreting CCL19, CCL19-specific desensitization might be also responsible for the observed CCL21 preference (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The mechanism underlying βarr1-mediated desensitization is thought to involve the interaction between βarr and the receptor core; this core conformation, presumably, sterically blocks the G protein-binding site in the receptor core (21). To assess the importance of the FLR of βarr1 for receptor desensitization directly, we monitored the attenuation of agonist-stimulated heterotrimeric Gs protein signaling, measured here as cAMP accumulation, in either the DKO (for the β 2 AR) or a βarr1/βarr2/β 2 AR triple-knockout (for the β 2 V 2 R and V 2 R) HEK293 cell line expressing ICUE2, a fluorescence resonance energy transfer biosensor-detecting cytoplasmic cAMP (22). This ICUE2 biosensor measures cAMP concentration in real time, and thus represents equilibrium between production and degradation of cAMP.…”
Section: Resultsmentioning
confidence: 99%
“…In a recent epidemiological study, it was found that antihypertensive medication, including ␤ blockers, may reduce the risk of AD (12). Another survey in AD patients indicates that ␤ blockers may be associated with a delay of functional decline in the patients (13).…”
mentioning
confidence: 99%